Physiological growth indices of quality protein maize (Zea mays L.) as influenced by different moisture regimes and weed control under semi-arid conditions - Rawal, Sandeep; Dhindwal, A.S.; Punia, S.S.; Yadav, Ashok (Annals of Agricultural Research, 2018)
A field experiment was conducted during kharif 2013 and 2014 at Agronomy research farm, CCS Haryana Agricultural University, Hisar to evaluate the growth indices of furrow irrigated raised bed (FIRB) planted maize under four moisture regimes viz., irrigation at 80, 120, 160 and 200 mmcumulative pan evaporation (CPE) intervaland five weed control treatments viz., weed free, weedy check, pre emergence application of pendimethalin at 1000 g ha–1, pre emergence application of atrazine at 750 g ha–1 and post emergence application of tembotrione at 120 g ha–1. Irrigation applied at 80 mm CPE resulted in significantly higher growth indices viz., absolute growth rate (AGR), crop growth rate (CGR) and relative growth rate (RGR) for 21-40 days after sowing (DAS) period culminating into higher grain yield (5210 kg ha–1 and 5452 kg ha–1 during 2013 and 2014 respectively) over rest of the moisture regimes, while the net assimilation rate (NAR) did not vary substantially with different moisture regimes. Among weed control treatments, weed free treatment resulted in significantly higher AGR and CGR for 21-40 DAS period while RGR and NAR for 21-40 and 41-60 DAS period, with concomitant increase in grain yield at harvest, as compared to weedy check and pre emergence application of pendimethalin at 1000 g ha–1 but was at par with pre emergence application of atrazine at 750 g ha–1 and post emergence application of tembotrione at 120 g ha–1. R2 (coefficient of determination) value clearly shows that yield is highly correlated with various growth indices and the knowledge can be further exploited to achieve higher yields.